Strategi Pengembangan Layanan Bimbingan Belajar Dalam Menghadapi Revolusi Industri 5.0 - riftiatul laili; rusmiyati rusmiyati; choli astutik (STKIP PGRI SUMENEP, 2022)
The purpose of this study was to determine the strategy for developing tutoring services in the face of the 5.0 industrial revolution era and the supporting factors in improving the quality of student learning in the 5.0 Industrial revolution era. This study uses a qualitative approach to describe thoroughly the data obtained in the field. The data collection method in this study used interview, observation and documentation techniques. The results showed that the strategy for developing tutoring services at SMK Negeri 1 Sumenep was fairly good, because it was carried out optimally by teachers at SMK Negeri 1 Sumenep. The strategies used in the development of tutoring services include providing additional classes, serving students who want to do online tutoring, providing special services in groups and individually, providing methods and techniques in the implementation of tutoring. The supporting factors in improving the quality of student learning in the era of the Industrial Revolution 5.0 are by utilizing the media, as well as the facilities and infrastructure of the school and an evaluation of student success.. Keyword: Tutoring Services and the Industrial Revolution 5.0